2021
DOI: 10.3390/v13081516
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Rabies Serology: Defining Context of Interpretation

Abstract: The case fatality rate of rabies, nearly 100%, is one of the most unique characteristic of this ancient virus infection. The crucial role rabies virus neutralizing antibody plays in protection is both well established and explanation of why rabies serology is important. Various laboratory methods can and have been used but serum neutralization methods have long been the gold standard due to the ability to measure function (neutralization), however these methods can be difficult to perform for several reasons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…This level is now endorsed by ACIP and replaces the previous minimum acceptable rabies antibody titer. The higher value provides a more conservative limit for indicating inadequate response to rabies vaccination and the need for booster doses ( 9 ).…”
Section: Minimum Acceptable Rabies Antibody Titer Levelmentioning
confidence: 99%
“…This level is now endorsed by ACIP and replaces the previous minimum acceptable rabies antibody titer. The higher value provides a more conservative limit for indicating inadequate response to rabies vaccination and the need for booster doses ( 9 ).…”
Section: Minimum Acceptable Rabies Antibody Titer Levelmentioning
confidence: 99%
“…The correlation of the test between ELISA and RFFIT is often used as the basis for assessing serological diagnostic performance for the detection of rabies-specific antibodies. However, it should be understood that the two methods are actually not always comparable, especially the differences in immunoglobulin classes detected by the two methods [ 26 ]. The RFFIT is also known as a functional assay in which the ability of antibodies to inhibit rabies virus infection is determined (known as virus-neutralizing antibodies), while the ELISA is a nonfunctional assay that detects certain classes of binding antibodies to viral antigens [ 1 , 18 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, RVNA titers approximately equivalent to or slightly lower than our threshold (0.05–0.11 IU/mL) had been associated with protection against a RABV challenge in an experimental study with raccoons from a population managed with ORV (Blanton et al 2018). A meta-analysis of several experimental studies reported cutoff thresholds of 0.25–0.5 IU/mL as potential surrogates of protection against RABV challenge in orally vaccinated raccoons (Moore et al 2017; Moore 2021). We have used the 0.125 IU/mL cutoff for purpose of ORV monitoring as an index to population immunity and for consistency and comparability with prior related studies.…”
Section: Methodsmentioning
confidence: 99%